Antenatal Care Practices in Hilly Area of Eastern Region of Nepal - Sah, RB; Gauray, K; Baral, DD; Jha, N; Pokharel, PK (Journal of Chitwan Medical College, 2013)
Antenatal care is provided during pregnancy to save lives of mother and foetus. The World Health Organization recommends four focused visits as sufficient for normal pregnancy. The objective of this study was to find out the antenatal care practices and its impact on birth outcome.The cross-sectional study was conducted from 28th March to 10th April, 2013 among the residents of Dhankuta municipality where 246 households were taken as subjects. Convenient purposive sampling technique was applied. Semi-structured questionnaire was used and face to face interview was conducted. Chi-square test was applied to find out the significant difference between sociodemographic characteristics and outcome variable i.e. birth outcome & antenatal care visits. Almost eighty eight percent of respondents attended ANC visits.The findings revealed that even though the fourth ANC visit was (82.4%), almost 82.5% of the pregnant women took the tetanus toxoid (TT) injections, about 81.7% received iron tablets and nearly 57.7% received albendazole. Women with School Leaving Certificate and higher education level are more likely to ANC visits (95.4%) than women with below SLC (87.9%) and no education (66.7%). Hindu women are more likely to have ANC visits (91.2%) compared to women of other religion (47.4%) (P